EFFECT OF COMPLIANCE COST AND TAX BURDEN ON TAX COMPLIANCE OF SMALL AND MEDIUM-SCALE ENTERPRISES IN BENUE STATE, NIGERIA - Okpe Caleb John; Aliyu Nuraddeen Shehu; Bello A. Ahmad; Ahmed Aliyu Abdullahi; Mohammed Musa Abdulkarim (Gusau Journal of Accounting and Finance, 2024)
Tax compliance is critical for small and medium-scale enterprises (SMEs) in Benue State, Nigeria, significantly affecting their growth and sustainability. The SME sector is pivotal to the economic growth and development of any nation and Nigeria is no exception. As a result, this study examined the effect of cost of compliance and tax burden on tax compliance of small and medium-scale enterprises (SMEs) in Benue State of Nigeria with the view to further provide empirical evidence on the factors affecting tax compliance. To achieve this, a survey of SMEs in the three senatorial districts of Benue state was conducted to collect data on the perceptions of SMEs on the effect of cost of compliance and tax burden on tax compliance in Benue State of Nigeria. The study’s population comprised the 25,913 registered SMEs in Benue state of Nigeria. The sample size was 552 SMEs. This study employed the use a cross-sectional survey and correlational research designs. The sampling technique adopted stratified proportionate random. Data were collected through the use of questionnaires and analyzed using Partial Least Squares -Structural Equation Modelling (PLS-SEM). The study found that the cost of compliance and tax burden showed a positive and significant effect on the tax compliance of SMEs in Benue State of Nigeria. The study recommends that tax authorities to work astutely towards making compliance more affordable and straightforward for SMEs while also strengthening enforcement measures to discourage non-compliance. Tax authorities should come up with a simple, sufficient, tax return system to help taxpayers to complete their tax returns accurately. Government should formulate policies that aim to reduce the cost of compliance while ensuring a balanced tax burden could enhance voluntary compliance, leading to a broader tax base and more sustainable public finance.